New Species of Tenuisvalvae (Duverger) (Coleoptera: Coccinellidae) Feeding on Parthenolecanium perlatum (Cockerell) (Hemiptera: Coccidae) in Citrus Crop - Santos, P. B.; Castro-Guedes, C. F.; Peronti, A. L. B. G. [UNESP]; Almeida, L. M. (Entomological Soc Brasil, 2017)
A new species of Hyperaspidini, Tenuisvalvae quadripunctata sp. nov. is described and illustrated. The genus is now represented by 11 species, all native of South America, and the new taxon is integrated into the existing key to species of the genus. Ecological data for T. quadripunctata sp. nov. and a list with prey and host plants to the species of the genus Tenuisvalvae are provided.
Keywords: Biological control; Hyperaspidini; predator; scale insects; taxonomy